Effect of protein structure on water and fat distribution during meat gelling. (1st August 2016) - Yang, Huijuan; Zhang, Wangang; Li, Teng; Zheng, Haibo; Khan, Muhammad Ammar; Xu, Xinglian; Sun, Jingxin; Zhou, Guanghong
Graphical abstract: Highlights: Heating for 0–30 min caused the setting of protein gel in meat emulsions. LF-NMR distinguished fat and water proton mobility in meat emulsion systems. Raman spectroscopy quantified the changes in secondary protein structures. PCA determined the critical time for gel setting in heated meat emulsions. Abstract: Emulsion-type sausages were produced, at 80 °C for either 0, 10, 20 or 30 min, using homogeneous Taihu pork batters. Low-field nuclear magnetic resonance (LF-NMR), with or without deuterium oxide (D2 O) substitution, evaluated the proton mobility states related to both water and fat molecules, or fat molecules only, respectively, in the sausage samples, during heat-induced gelation. The decreasing trend in the area proportion of main peak T 21, reflected a tighter gel structure in emulsion-type sausages. Raman spectra (400–3600 cm –1 ) revealed decreased α-helix, but increased β-sheet, β-turns and random coil contents, during the gelling process. Moreover, principal component analysis (PCA) showed significant correlations between secondary protein structures with distribution of water and fat in the gel matrix. Furthermore, this study established the relationship of water and fat protons mobility with changes in secondary protein structures, and described the critical time of gel formation in emulsion-type pork sausages.